Effect of weekly Plyometric training frequency on Adolescents female basketball players during in-season: A comparison of two vs. four sessions. - Bruno Figueira; Eduardo Abade; Nuno Mateus; Anthony Weldon; Jaime Sampaio; Rūtenis Paulauskas (PLoS ONE)
This study investigated the effects lower vs. higher frequencies of volume-equated plyometric training youth female basketball players. Thirty youth highly trained female basketball players (age, 15.7 ± 0.5 years; body mass, 64.1 ± 8.6 kg; height, 172.8 ± 6.2 cm, basketball training experience 6.3 ± 1.7 years) integrating a youth national development program participated in the study. A parallel-group randomized trial was undertaken to assess the effect of an eight-week plyometric intervention on jumping (counter-movement jump, drop-jump, horizontal jump), running (5 and 20-meter sprint), and change of direction performance. The study compared the outcomes of two versus four volume-equated training sessions per week, followed by a one-week retention period. A Bayesian Mixed Factor ANOVA revealed decisive evidence that the change of direction improved performance between the pre-test and post-test, as well as pre-test and retention. No discernible differences emerged between intervention groups. For the counter-movement jump, moderate evidence supported performance improvements in the 2PLYO group. In drop jump, both groups demonstrated decisive improvements between the pre-test and post-test, with moderate evidence for pre-test and retention, but no group differences were observed. These findings suggest that an 8-week plyometric training program, in both frequencies, leads to significant improvements in change-of-direction, countermovement jump, and drop jump performance among female junior basketball players participating in a youth national development program. However, it remains inconclusive whether a two-day training frequency provides a distinct advantage over four-days. Further research or consideration of additional factors may be necessary to ascertain the optimal training frequency for maximizing benefits.